2016
DOI: 10.1111/pim.12349
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis – immunology of a foodborne parasitosis

Abstract: SummaryAnisakis species are marine nematodes which can cause zoonotic infection in humans if consumed in raw, pickled or undercooked fish and seafood. Infection with Anisakis is associated with abdominal pain, nausea and diarrhoea and can lead to massive infiltration of eosinophils and formation of granulomas in the gastrointestinal tract if the larvae are not removed. Re-infection leads to systemic allergic reactions such as urticarial or anaphylaxis in some individuals, making Anisakis an important source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 144 publications
(386 reference statements)
1
69
0
11
Order By: Relevance
“…Indeed, specific A. pegreffii ‐IgE response has been found in the serum of sensitized patients, accompanied by a predominant Th2‐type response to the parasite . Results from murine models have confirmed that predominant Th2 immune responses are induced by infestation with the live larvae, while a mixed Th1/Th2 polarization is observed when the parasite crude extracts are used as immunogen …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed, specific A. pegreffii ‐IgE response has been found in the serum of sensitized patients, accompanied by a predominant Th2‐type response to the parasite . Results from murine models have confirmed that predominant Th2 immune responses are induced by infestation with the live larvae, while a mixed Th1/Th2 polarization is observed when the parasite crude extracts are used as immunogen …”
Section: Introductionmentioning
confidence: 93%
“…The pathological outcomes within the gastrointestinal tract during an infection by Anisakis spp. larvae are the combined result of the direct invasive capacity of the larva, the antigens released during its invasion and the interaction with the host's immune response . The larvae release proteolytic enzymes to invade the gastrointestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some worms can survive inside the human gastrointestinal tract. Especially anisakid nematodes of the genus Anisakis (Anisakidae, Ascaridoidea) have been reported to cause anisakiasis, an inflammation of the human gastrointestinal tract, in many regions worldwide (Ishikura & Namiki 1989, Ishikura & Kikuchi 1990, Klimpel & Palm 2011, Ivanovic et al 2015, Lim et al 2015, Sohn et al 2015, Nieuwenhuizen 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The immunopathology of Anisakis infection, an important foodborne zoonosis, is reviewed by Natalie Nieuwenhuizen, emphasizing the potential for abdominal pain, granuloma formation and, with repeated infection, severe systemic allergic reactions. The hazards of occupational exposure to Anisakis allergens in fish, without oral consumption, leading in some cases to dermatitis, rhinitis, conjunctivitis or asthma, are also detailed.…”
mentioning
confidence: 99%